Characteristics of group performance in children's theater performances - Hassan, Wissam Hamid (Al-Adab Journal, 2022)
Child Theater is a theater that serves childhood، whether it is held by adults or young people as long as the goal is to entertain the child and entertain him and raise his knowledge and his feelings and movement، or intended to diagnose the child's roles and representative players and dramatic positions to communicate with adults or young. Theatrical dramas were his staff in the service of the formative images of the theater scene. The function given to the assemblies was to increase theatrical performance in terms of building events to reach the peak. The scenes of the groups were not only in the modern plays، but also extended their roots to the ancient Greek plays.